(untitled) (Bangladesh Medical Journal Khulna, 2021)
Background: Polycystic ovarian syndrome (PCOS) is one of the most common endocrinopathy in reproductive age women. PCOS has complex etiopathology, diverse clinical presentation and diagnostic criteria. Objective: Objective of this study was to find out the determinant clinical feature and investigations for improving diagnostic accuracy and assessment of PCOS, thereby evolving opportunity for proper treatment. Methods: This prospective cross sectional observational study was conducted in Islami Bank hospital, Khulna, from January 2017 to February 2020. Women seeking gynecological consultation in outdoor with at least one complaint of oligomenorrhoea, hirsutism, weight gain or infertility were enrolled for study. Subjects were selected on the basis of inclusion and exclusion criteria. A structured proforma, based on relevant history, laboratory work up, risk factors and co morbidities were prepared before-hand. Diagnosis of PCOS was based on Rotterdam criteria, 2003. The clinical manifestations of PCOS, frequency of different sub phenotypes and associated morbidities were measured as outcome. Results: Total study population was 202. Age of subjects were in between 13- 37 years. Thirty seven (18%) were adolescent, one hundred forty (65.7%) patients were overweight and obese. Majority of cases were married. Complaint of infertility was present in 125 (61.9%) cases. Oligomenorrhoea, hirsutism, poly cystic ovary was present in 145 (71.8%), 137 (67%), and 130 (64.4%) patients respectively. LH/FSH ratio >2 in 45 (22.3%) cases, Serum free testosterone >0.79 ngm/ml were associated with hirsutism. PCOS with clinical sub phenotypes A, B, C, and D were 38(18.9%), 72 (35.6%), 27 (13.4%) and 65 (32.2%) cases respectively. Case morbidities were Hypertension 75 (37.1%), Diabetes mellitus 18 (8.9%) and Metabolic syndrome 44 (20.1%). Link with Hypothyroidism Hyperprolactinemia were identified in 47 (19%) cases. Conclusion: Oligo-anovulatory woman with hyperandrogenism with or without poly cystic ovary were diagnosed as a largest group of PCOS-A and B sub phenotypes. Infertility, hypothyroidism, hypertension, diabetes mellitus, metabolic syndrome and endometerial hyperplasia were common. Bang Med J Khulna 2020: 53 : 17-22